OBSERVASI PENGAWAS SEKOLAH TERHADAP PENERAPAN MODEL PEMBELAJARAN SQ3R DI SDN 094131 BATU SILANGIT - Basaria Hutapea (JURNAL TEMATIK, 2019)
The purpose of this study is to find out through the Observation of School Supervisors on the Implementation of the SQ3R Learning Model at SDN 094131 Batu Silangit This type of research is a classroom action research consisting of 2 cycles. The subjects of the study were 6 public elementary school teachers. Data collection methods are used, observation sheets, and photos. At the initial ability or before being given an action, it can be seen that the average grade of the class is 70.9 and the percentage of categories is quite 100%, either 0%. The first cycle of action with the application of the SQ3R learning model through supervisor observation techniques obtained an average grade of 85.2 with a percentage of 0% enough categories and 100% enough categories. This shows an increase in pre-action test results both in terms of average class and teacher performance. In the second cycle with the application of the SQ3R learning model through supervisor observation techniques, it was found that the average grade of the class increased by 92.7 and the observation value of the teacher's activity increased to reach 100%. And the application of the SQ3R model of learning methods has a positive effect, which can increase student motivation Regency which is shown by the results of interviews with several students, the average answer states that students are interested and interested in the learning methods of the SQ3R model so they become motivated to learn.